Penanaman Nilai-Nilai Agama Islam Melalui Kegiatan Ekstrakurikuler Pramuka Di SMP PGRI Jogoroto – Jombang - Solechan Solechan; Etik Fatmawati (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2021)
Scout education in Indonesia is an important aspect of national education and is part of the history of Indonesia's struggle. In its development, scouting education has begun to be less attractive and is considered a monotonous activity and what is learned is only that. Whereas behind the simplicity of scouting education, scouting activities can be observed seriously and will develop all the potential that has been bestowed by Allah to humans related to Islamic religious values ??contained in the basic principles of scouting. The purpose of this research is to describe the cultivation of Islamic religious values ??through scout extracurricular activities at SMP PGRI Jogoroto. Supporting and inhibiting factors for planting Islamic religious values ??through scout extracurricular activities at SMP PGRI Jogoroto. This type of research includes field research using a qualitative approach. Data collection techniques through interviews, observation, and documentation. Data analysis using data reduction, data display and verification. Furthermore, the data validity test technique is through participation extension, observation persistence, and triangulation. The result of this research is the method of planting Islamic religious values, namely the method of advising, the method of letting go, and the method of modeling. The material for planting Islamic religious values ??is the values ??of faith and moral values. Supporting factors: psychological factors in the form of student motivation, social environmental factors, learning approach factors. Inhibiting factors, namely the lack of parental education for children, a less supportive environment, and differences in student IQ.